2015
DOI: 10.1007/s00787-015-0738-9
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity and correlates of disruptive mood dysregulation disorder in 6–8-year-old children with ADHD

Abstract: This study aimed to characterize the nature and impact of disruptive mood dysregulation disorder (DMDD) in children with attention-deficit/hyperactivity disorder (ADHD) including its co-occurrence with other comorbidities and its independent influence on daily functioning. Children with ADHD (6-8 years) were recruited through 43 Melbourne schools, using a 2-stage screening (parent and teacher Conners 3 ADHD index) and case-confirmation (Diagnostic Interview Schedule for Children, Version IV; [DISC-IV]) procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 35 publications
6
30
0
2
Order By: Relevance
“…In Mulrany's study [21], 20% of children with ADHD met the criteria for DMDD and it was found that males were at a greater risk of developing ADHD with DMDD which is consistent with previous data. Those results also demonstrated that DMDD exacerbates social difficulties in children with ADHD and has a stronger impact on family functioning.…”
Section: Similaritiessupporting
confidence: 87%
“…In Mulrany's study [21], 20% of children with ADHD met the criteria for DMDD and it was found that males were at a greater risk of developing ADHD with DMDD which is consistent with previous data. Those results also demonstrated that DMDD exacerbates social difficulties in children with ADHD and has a stronger impact on family functioning.…”
Section: Similaritiessupporting
confidence: 87%
“…Studies demonstrate that having a diagnosis of DMDD in childhood is associated with high levels of social impairment (Copeland, Angold, Costello, & Egger, 2013; Mulraney et al, 2016). Youth with SMD/DMDD frequently present to treatment for outbursts at school resulting in suspensions and for outbursts at home, which can include verbal rages, destruction of property, or physical aggression.…”
mentioning
confidence: 99%
“…For Bella, however, her prolonged instances of angry and irritable mood in between temper outbursts indicated a diagnosis of DMDD. It is also important to note that early onset of ADHD and co-occurring symptoms of anxiety are also consistent with the diagnosis of DMDD (Dougherty et al, 2014; Mulraney et al, 2015; Uran & Kılıç, 2015). …”
Section: Case Conceptualizationmentioning
confidence: 74%